Energy audit in Faculty of Mechanical Engineering UiTM Shah Alam, Selangor - Sharif, Ahmad Fauzi (2010)
People nowadays are more concerned about energy efficiency and conservation. One of the focal points of such concern is on energy consumption in buildings. An energy audit is considered as one of the comprehensive methods in checking energy usage and wastage in buildings. This project addresses the implementation method of energy saving in Faculty of Mechanical Engineering (FKM) at Universiti Teknologi MARA (UiTM) Shah Alam, Malaysia. Power quality, harmonic and power factor issues are successfully identified and recommendation for improvement is highlighted. The power quality data is obtained by Fluke 1750 recorder install at the Main Switch Board (MSB) Faculty of Mechanical Engineering. After the installation is done, the data will be recorded for a day. As a result, the lower power factor, high harmonics distortion in phase currents and imbalance load in three phases at the Faculty of Mechanical Engineering are the causes of high electrical energy consumption which is contribute to the total overall monthly electrical bill of the Complex of Engineering building. The lighting system design also contribute to the high energy consumption because from the inspection made on the artificial lighting, all the lighting at the open corridor does not take into consideration of sufficient illumination provided by the natural day-lighting. The lighting at all open corridors for various levels are switched-on during day-lighting. In this project, energy saving concept and purpose is analyzed. By analyzing current utilization situation of energy in FKM building, the significance of energy audit in FKM building to produce improvement in operation efficiency and cost saving initiatives due to high monthly electrical consumption and penalty charge due to low power factor operation by the supply utility. The monthly bill at the Engineering Complex Tower should be reduces at least 20%.